(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article examines the necessity to implement competency-based approach that is caused by the following factors: transition of world community to the information society where the ability to learn, skills of information seeking, the ability to life-long self-learning, the necessity to integrate into different societies, to be competitive in the world labour market are in high demand; refocusing of education from obtaining knowledge and skills to the formation of problem solving skills on the basis of acquired knowledge. The analysis of scientific literature shows that the selection of approaches to the Ukrainian language training of foreign citizens is determined by its key functions: to be the most important means of communication, cognition and influence and form developed, socially active personality that is able to communicate in various types of speech activity, keep to the standards and rules of linguistic behavior of certain society representatives, relies on information about the level of individual’s development, cultural and social peculiarities and differences. So, the aim of language training of foreign students is the competence formation necessary for their harmonius coexistence in a “foreign” society, since knowledge and skills of Ukrainian language and culture, the ability to determine the differences that impede understanding during the communication, the automation of communication skills for specific situations are the keys to the successful development of the personality in foreign language sociocultural environment. The introduction of competency-based approach to the process of Ukrainian language training of foreign student provides the creation of conditions that ensure the solution of professional tasks on the bases of acquired knowledge and skills; education of intelligent person that is able to communicate in a multifactor world and process information effectively, generate ideas, and overcome the life and professional obstacles. The key goal of implementing competency-based approach is the formation of language, speech, communicative, intercultural and strategic competences to develop personality that is able take part in intercultural dialogue both in personal and professional spheres.